Age dependent efficacy of implantable cardioverter-defibrillator treatment: observations in 450 patients over an 11 year period. Issue 4 (1st October 1997) - Trappe, Hans-Joachim; Pfitzner, Petra; Achtelik, Michael; Fieguth, Hans-Gerd
Abstract : Objective: To determine whether implantable cardioverter-defibrillator (ICD) treatment is beneficial in elderly patients with life threatening ventricular tachyarrhythmias. Design: Since January 1984, ICDs were implanted in 450 patients to evaluate surgical risk, complications and mean survival in relation to patient age; 81 patients (18%) were ⩽ 50 years at the time of ICD implant, 254 patients (56%) were between 51 and 64 years, and the remaining 115 (26%) were ⩾ 65 years. Epicardial lead systems were implanted in 209 patients (46%), while transvenous lead systems were implanted in 241 (54%). Results: 13 patients (3%) died perioperatively, more often after epicardial (11 of 209 patients, 5%) than after transvenous ICD implantation (one of 241 patients, < 1%) (p < 0.05). During a mean (SD) follow up of 28 (24) months (range < 1 to 114 months), 90 patients (20%) died. Of these, nine (2%) died from sudden arrhythmic death; five (1%) died suddenly, probably as a result of non-arrhythmic causes; 55 (12%) died from other cardiac causes (congestive heart failure, myocardial infarction); and 21 (5%) died from non-cardiac causes. The three, five, and seven year survival for arrhythmic mortality was 95% in patients ⩽ 50 years compared with a three year survival of 93% and a five and seven year survival of 91% in patients of 51 to 64 years, and a three, five, and seven year survival of 99% in patients ⩾ 65 years. 362 patients (80%) received ICD discharges (21 (43) shocks per patient), with a similar incidence among all three patient groups (⩽ 50 years, 80%; 51 to 64 years, 81%; ⩾ 65 years, 79%). The time interval between ICD implant and the first ICD treatment was shorter in patients ⩾ 65 years (8 (8) months) than in patients between 51 and 64 years (11 (14) months) or ⩽ 50 years (11 (11) months) (p < 0.05). Survival time following first appropriate shock was 30 (24) months in patients ⩽ 50 years, 30 (26) months in patients of 51 to 64 years, and 19 (20) months in patients ⩾ 65 years. Conclusions: Elderly patients benefit from ICD treatment, and survive for a considerable time after the first treatment. Therefore, elderly patients should be considered candidates for ICD implantation if life threatening ventricular tachyarrhythmias are present.